Naringenin attenuates hepatitis B virus X protein-induced hepatic steatosis - Hung-Jen Lin; Ko-Li Ku; I-Hsin Lin; Chia-Chou Yeh (BMC, 2017)
Abstract Background Naringenin (Nar), a common dietary flavonoid abundantly present in fruits, vegetables, and Chinese herbs, is believed to possess strong anti-inflammatory properties and to modulate hepatic apolipoprotein and lipid synthesis. However, there are no reports describing Nar's effects on the hepatitis B virus protein X (HBx) -induced hepatic steatosis, and the detailed molecular mechanisms of the compound's effects are still unclear. Methods Nar was administered by oral gavage to HBx-transgenic mice from 4 to 6 weeks of age. Mice were sacrificed after 14 days of once-daily naringenin administration. Liver tissues and sera were collected for histopathology and biochemical analysis. Results Nar counteracted hepatic lipid accumulation and liver dysfunction in HBx-transgenic mice. In addition, Nar significantly decreased expression of adipogenic and lipogenic genes in mice, suggesting that the compound may have therapeutic effects in the early stages of HBx-mediated hepatic steatosis. These results indicated that naringenin inhibits HBx-induced expression of hepatic adipogenic and lipogenic genes through suppression of HBx-induced gene expression, including decreases in the transcriptional activity of SREBP1c, LXRα, and PPARγ in HBx-trangenic mice and HBx-transfected HepG2 cells. Conclusions Results from this study suggested that Nar may serve as a therapeutic agent for preventing HBx-infected hepatic steatosis in humans.